Design of Solid Geometry Learning Media To Improve Student Understanding Based On Augmented Reality - Arif Setiawan (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
In the learning process at school, students have difficulty visualizing solid geometry into areal form. This study aims to develop an android-based solid geometry learning media withAugmented Reality technology and to test the feasibility of the learning media. The methodused in this research is Research and Development (R&D) with the development modelapplying 5 stages of ADDIE namely analysis, design, development, implementation andevaluation. The results of this study are an AR learning media application that has featurenamely formula and practice questions and the use of two tests, namely blackbox tests andapplication tests for feasibility tests. Blackbox testing and testing obtain the same resultswith a percentage of 100%. Thus, the application of learning media can conclude that it isvery feasible to use